Overexpression of DcR3 and Its Significance on Tumor Cell Differentiation and Proliferation in Glioma - Suning Huang; Gang Chen; Yiwu Dang; Long-Hua Chen (The Scientific World Journal)
Background. Overexpression of decoy receptor 3 (DcR3) have been reported in various classes of malignancies. However, its expression and clinicopathological contribution in gliomas has not been fully elucidated. Objective. To explore the expression and clinical significance of DcR3 protein in relation to tumor cell differentiation and proliferation in glioma cell lines and tissues. Methods. One hundred and twenty-five samples of glioma patients and 18 cases of normal brain tissues were recruited. The expression of DcR3 protein was detected using immunohistochemistry. Tumor differentiation was assessed by histologic characters and the status of glial fibrillary acidic protein (GFAP). Tumor cell labeling indexes (LIs) of Ki-67 and PCNA were also obtained. The relationship between the DcR3 level and clinicopathological features was investigated, including tumor differentiation, LIs, and survival. Meanwhile, the expression of DcR3 protein was also measured in the supernatants of 8 glioma cell lines and glioma cells freshly prepared from 8 human glioblastoma specimens by using western blot. Results. The level of DcR3 protein in gliomas was significantly higher than that in normal brain tissues (P<0.01). DcR3 expression showed positive correlations with tumor pathological grade (r=0.621, P<0.01) and negative with GFAP expression (r=-0.489, P<0.01). Furthermore, there were positive correlations between DcR3 expression and Ki-67, PCNA LIs (r=0.529, P<0.01; r=0.556, P<0.01). The survival in the DcR3 negative group was 50 ± 1.79 months, longer than that of the DcR3 positive group (48.36 ± 2.90), however, without significance (P=0.149). Different levels of DcR3 could also be detected in the culturing supernatants of all the 8 glioma cell lines and glioma cells freshly obtained from 8 human glioblastoma specimens. Conclusions. The overexpression of DcR3 might play a crucial role in the tumorigenesis, differentiation, and proliferation of glioma.